The time has grown short: René Girard, or the last law - Chantre, Benoît (Breakthroughs in mimetic theory, 2022)
"In this exploration of Girard's insights, his French editor and longtime collaborator Benoît Chantre brings Saint Paul's Letter to the Romans into dialogue with both Proust and Girard in order to push to its logical endpoint the idea of a back-and-forth movement from chaos to order"--